Pemberdayaan Masyarakat Dalam Program PTSL Di Kelurahan Jembatan Kecil Kecamatan Singaran Pati - Anggraini, Sari; Anggraini, Ida (Jurnal Kewirausahaan & Inovasi, 2025)
This Thematic Community Service Program (KKN) aims to observe the process and strategies for successful field registration applied to the PTSL program in Jembatan Kecil Village. Electronic-Based PTSL is a land registration activity for the first time or in other words, land rights have never been registered, simultaneously for all land registration objects throughout Indonesia in one village / kelurahan area, including the collection of physical data and juridical data. It is hoped that through this program the land field can be mapped entirely. So that the output that you want to produce from this activity is a scientific article in the Journal of Community Service, a video of activities published on GoogleDrive and a Final Report in the form of a Report on the Results of the Implementation of UNIVED Thematic KKN Bengkulu Period 1. The methods used in Thematic KKN are participation, observation, interview, literature study and documentation.